2013
DOI: 10.1021/nl4032296
|View full text |Cite
|
Sign up to set email alerts
|

Band Gap Engineering and Layer-by-Layer Mapping of Selenium-Doped Molybdenum Disulfide

Abstract: Ternary two-dimensional dichalcogenide alloys exhibit compositionally modulated electronic structure, and hence, control of dopant concentration within each individual layer of these compounds provides a powerful tool to efficiently modify their physical and chemical properties. The main challenge arises when quantifying and locating the dopant atoms within each layer in order to better understand and fine-tune the desired properties. Here we report the synthesis of molybdenum disulfide substitutionally doped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
460
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 504 publications
(483 citation statements)
references
References 41 publications
21
460
1
1
Order By: Relevance
“…Among them, the direct grown method of TMDs (e.g. MoS 2 ) synthesis via sulfurization of transition metal films has great advantages for a large scale to have possibilities for the band gap engineering, 29 hetero-structures, 30 and doping. 25 Laskar et al 25 first reported on in situ p-type doping in cation-site by Nb diffusion in direct grown MoS 2 thin films.…”
mentioning
confidence: 99%
“…Among them, the direct grown method of TMDs (e.g. MoS 2 ) synthesis via sulfurization of transition metal films has great advantages for a large scale to have possibilities for the band gap engineering, 29 hetero-structures, 30 and doping. 25 Laskar et al 25 first reported on in situ p-type doping in cation-site by Nb diffusion in direct grown MoS 2 thin films.…”
mentioning
confidence: 99%
“…[57,62,63] Ajayan et al also achieved synthesis of MoS2(1-x)Se2x alloy, Se component can be controlled from 0 to 75% by changing ratio of S and Se precursors before growth procedure, and prolonged growing time could result to film growth due to increased nucleation density. [64] However, the optical bandgap of the alloy can be turned over 200 meV. Except for common Raman and PL measurements, X-ray photoelectron spectroscopy (XPS) is valid to confirm Se content by comparing Se 3p3/2 and 3d peak intensity revolution, while atomic annular dark field (ADF) imaging is useful to analyze dopant distribution.…”
Section: Mos2 Alloyingmentioning
confidence: 99%
“…Except for common Raman and PL measurements, X-ray photoelectron spectroscopy (XPS) is valid to confirm Se content by comparing Se 3p3/2 and 3d peak intensity revolution, while atomic annular dark field (ADF) imaging is useful to analyze dopant distribution. [64] Different from doping in the growth process, atom substitution can be conducted after growth of MoS2, and annealing using the dopant sources in the furnace is also efficient to turn band structure of the material. [65] Except for chalcogenide atom substitution, transition metal atoms can also be substituted using CVT methods to modulate properties of MoS2 and these alloys shows good thermodynamic stability at ambient conditions.…”
Section: Mos2 Alloyingmentioning
confidence: 99%
“…Band gap engineered nanosheets were successfully produced using precursors from mechanically exfoliated MoS 2 (1-x) Se 2x bulk alloy showing triangular nanosheets (SEM) with the edge lengths of 30-80 micron. Lateral composition-graded 2D-MoS 2(1-x) Se 2x nano layers were also synthesized employing a simple moving source thermal evaporation method of an improved CVD [55][56][57][58][59][60][61][62][63][64][65][66][67][68]. Subsequently, 2D-WS 2x Se 2(1-x) alloys were prepared from WO 3 (monoclinic crystal) to WS 2 (1-x) Se 2x (hexagonal crystal) through simultaneous sulfurization and selenization, in which, the chemical activity of S made it easy to tune the value of x by varying the weight of sulfur powder [69].…”
Section: Other Hybrid 2d-materialsmentioning
confidence: 99%